2006
DOI: 10.3346/jkms.2006.21.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus among Health Care Workers in Korea

Abstract: We studied the seroprevalence of HBsAg, anti-HBs and anti-HBc and the vaccination histories among health care workers (HCWs) at a large suburban referral hospital in Korea. The purpose of this study was to determine the immune status of HCWs against hepatitis B virus and we also wanted to prepare a practical guideline to protect HCWs from occupational exposure. During December, 2003, 571 HCWs (56 physicians, 289 nurses, 113 technicians and 113 aid-nurses) aged between 21 and 74 yr were included in the surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 15 publications
5
27
2
6
Order By: Relevance
“…Sağlık personelinde koruyucu düzeyde antiHBs pozitifliğinin Polonya'da %98, Kore'de %76.9, Güney Afrika'da %30, ülkemizdeyse %57.8-%73 arasında olduğu bildirilmektedir (7,(15)(16)(17)(18).…”
Section: İrdelemeunclassified
“…Sağlık personelinde koruyucu düzeyde antiHBs pozitifliğinin Polonya'da %98, Kore'de %76.9, Güney Afrika'da %30, ülkemizdeyse %57.8-%73 arasında olduğu bildirilmektedir (7,(15)(16)(17)(18).…”
Section: İrdelemeunclassified
“…In this study, it was found that 29 per cent of HCWs had experienced NSI at some point in their careers and among the HCWs, nurses were most prone to NSI. Several other studies had also shown high occurrence of NSI among nurses [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 98%
“…Shrestha et al in 2006 evaluated 145 health care workers and found positive Anti-HBc-Ab in 14.5%, and positive HBsAg in 1.4% of all examinees [42]. In 2006 in a referent Hospital in Korea, HBsAg was detected in 2.4% of 571 examined health care workers [43]. Djeriri et al in 1996 referred positive anti-HBc-Ab, HBsAg and Anti-HCV-Ab in 7%, 0 and 0.7% of evaluated health care workers, respectively [44].…”
Section: Discussionmentioning
confidence: 99%